A Critique of Methodological Individualism: The Concept of Altruism and Application of the Ultimatum Game - Yıldız Zeliha Hatipoğlu (İnsan & Toplum)
Although methodological individualism has served the scientific claims of mainstream economics, it is far removed from modeling actual people. To raise the level of abstraction, mainstream economics has started expressing human nature through homo economicus by adding the selfishness assumption to methodological individualism. From this point of view, homo economicus makes the choice that provides the highest benefit to the self among the preferences one has correctly calculated and organized by following the assumptions of completeness, transitivity, continuity, reflectivity. However, an actor decides in a dynamic environment through one’s limited rational capacities using cognitive shortcuts and takes altruistic actions for others’ benefit without expecting anything in return or even bearing a cost. In this research, altruism as one of the basic concepts in psychology, sociology, and ethics is examined within the scope of behavioral economics. In order to examine altruistic preferences, the subjects played the ultimatum game and were asked to offer a portion of their 100 units of money (36% was the average offer, close to the world average for this game) with another anonymous player. The offers was rejected at a rate of 28%, which is higher than other rates for this game in Turkey and the world. Individuals are understood to punish others by sacrificing their output in the face of unjust distribution. Firstly, the argument that the obtained findings deviate from the assumption of homo economicus has been expanded by dealing with rationality and methodological individualism in economics, and then further expanded with altruism. After examining the ultimatum game and the questionnaire, the study concludes by suggesting different non-preference-based approaches to researchers